2019
DOI: 10.3390/su11123385
|View full text |Cite
|
Sign up to set email alerts
|

The Balance of Individual and Infrastructure Values in Decisions Regarding Advanced Science and Technology

Abstract: A country’s scientific technology policy rarely reflects public opinion. In this study, we created a hierarchical model of societal well-being, comprising five value components for both individual and infrastructure well-being, to analyze the balance among these values. We conducted a survey in two stages; first, both individual and infrastructure well-being were investigated, and then the weights between pairs of value categories composing individual and infrastructure well-being were scored to assess which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…This is because the current hydrogen station construction and FCV purchase costs are higher than those of the existing technology. Previous studies have shown that safety and economics are important in terms of infrastructure and individual values [30]. In addition, although this study built an acceptability model for HSs, it could not deal with the relationship between consciousness and actual behavior and the continuity of knowledge and technical reliability through experience.…”
Section: Discussionmentioning
confidence: 96%
“…This is because the current hydrogen station construction and FCV purchase costs are higher than those of the existing technology. Previous studies have shown that safety and economics are important in terms of infrastructure and individual values [30]. In addition, although this study built an acceptability model for HSs, it could not deal with the relationship between consciousness and actual behavior and the continuity of knowledge and technical reliability through experience.…”
Section: Discussionmentioning
confidence: 96%